Strategi Personal selling dalam Komunikasi Pemasaran: Upaya Meningkatkan Brand awareness di Production House Tryma Creative - Maheswari, Dita Meisya; Dharta, Firdaus Yuni; Poerana, Ana Fitriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The marketing strategy paradigm shift from conventional to digital has brought significant changes to the economic sector. The use of digital platforms as a marketing tool causes competition between companies to become increasingly fierce. To survive and develop, companies need to have an effective marketing communications strategy to increase brand awareness. Brand awareness is one of the key factors influencing consumer purchasing decisions; The higher the brand awareness of a product or service, the more likely consumers are to choose it. This research aims to explore personal selling strategies in marketing communications at the Tryma Creative Production House in order to increase brand awareness. The research method used is qualitative with a descriptive approach. Integrated Marketing Communications (IMC) theory is used as a framework for understanding and analyzing the strategies implemented. The research results show that the personal selling strategy used by Tryma Creative includes: 1) Conducting face-to-face meetings or via Zoom to build personal relationships with clients, 2) Providing high-quality service at the initial meeting to give a positive and professional impression, and 3) Utilizing communication via social media and WhatsApp to maintain continuous interaction with clients. This approach has been proven to significantly increase Tryma Creative's brand awareness, making the company better known and trusted by consumers. These findings provide important insights for other companies looking to optimize their personal selling strategies in the digital era.